Partnering essential oils with antibiotics: proven therapies against bovine Staphylococcus aureus mastitis - Abd El-Hamid, Marwa I.; El-Tarabili, Reham M.; Bahnass, Mosa M.; Alshahrani, Mohammed Abdulrahman; Saif, Ahmed; Alwutayd, Khairiah Mubarak; Safhi, Fatmah Ahmed; Mansour, Abdallah Tageldein; Alblwi, Noaf Abdullah N.; Ghoneim, Mohammed M.; Elmaaty, Ayman Abo; Al-harthi, Helal F.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
There is an urgent need to develop therapeutic options for biofilm-producing Staphylococcus aureus (S. aureus). Therefore, the renewed interest in essential oils (EOs), especially carvacrol, linalool and eugenol, has attracted the attention of our research group. Multidrug resistance and multivirulence profiles in addition to biofilm production of S. aureus strains isolated from cows with mastitis were evaluated using both phenotypic and genotypic methods. The antimicrobial and antibiofilm activities of EOs were tested using both in vitro and molecular docking studies. Moreover, the interactions between commonly used antibiotics and the tested EOs were detected using the checkerboard method. We found that all our isolates (n= 37) were biofilm methicillin resistant S. aureus (MRSA) producers and 40.5% were vancomycin resistant S. aureus (VRSA). Unfortunately, 73 and 43.2% of the recovered MRSA isolates showed multidrug resistant (MDR) and multivirulence patterns, respectively. The antimicrobial activities of the tested EOs matched with the phenotypic evaluation of the antibiofilm activities and molecular docking studies. Linalool showed the highest antimicrobial and antibiofilm activities, followed by carvacrol and eugenol EOs. Fortunately, synergistic interactions between the investigated EOs and methicillin or vancomycin were detected with fractional inhibitory concentration index (FICI) values ≤ 0.5. Moreover, the antimicrobial resistance patterns of 13 isolates changed to sensitive phenotypes after treatment with any of the investigated EOs. Treatment failure of bovine mastitis with resistant S. aureus can be avoided by combining the investigated EOs with available antimicrobial drugs. We hope that our findings can be translated into a formulation of new pharmaceutical dosage forms against biofilm-producing S. aureus pathogens.